Edukasi Anti Cyberbullying Dalam Iklan Layanan Masyarakat Pada Akun YouTube @cerdasberkarakter.kemdikdasmen - Sahiralayalia, Difla Uzbanasyat; Zuhri, Saifudin (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The rapid development of information and communication technology has made the internet one of the most widely used means of communication, including through social media platforms such as YouTube. YouTube provides features such as watching, uploading, and sharing videos, making it an effective medium for delivering messages to a wide audience. Amid the increasing cases of cyberbullying in Indonesia, YouTube has been utilized as an educational platform to raise public awareness. One example can be seen on the YouTube account @cerdasberkarakter.kemdikdasmen, which presents public service advertisements containing educational messages to build awareness among viewers. This study aims to examine how anti-cyberbullying education is presented in public service advertisements on the YouTube account @cerdasberkarakter.kemdikdasmen. The research uses a qualitative approach with content analysis methods by Parker, Saundage, and Lee. The findings show that anti-cyberbullying education in these public service advertisements is conveyed through five main themes: education on the role of schools in fostering anti-cyberbullying awareness, education through student empowerment as agents of change, education on the role of social support in overcoming cyberbullying, education on digital literacy, and education on the underlying factors that drive perpetrators of cyberbullying.